Millennial generation in Bangladesh : their life strategies, movement, and identity politics - Minamide, Kazuyo, 1975- (University Press Limited, 2022)
Papers presented at the International symposium "Perceiving Contemporary Young Generation in Bangladesh: their Life Strategies and Identity Politics under Globalization" in February 2019 at Department of Anthropology of Jahangirnagar University in Dhaka; funded and organized by Japan Society for the Promotion Science (JSPS).